Nanomaterials for biofuel production using lignocellulosic waste - Srivastava N.; Srivastava M.; Manikanta A.; Singh P.; Ramteke P.W.; Mishra P.K. (My University, 2025)
Production of biofuels using second-generation, non-food, lignocellulosic waste biomass is a sustainable approach that solve the economic issues of fossil fuels and environmental pollution. The major issues of biofuel production are biomass complexity, pretreatment, enzyme denaturation and cost. This article reviews the application of nanomaterials for biofuel production from various lignocellulosic wastes. © 2017, Springer International Publishing Switzerland.